A system dynamics-based environmental performance simulation of construction waste reduction management in China. (May 2016) - Ding, Zhikun; Yi, Guizhen; Tam, Vivian W.Y.; Huang, Tengyue
Highlights: This paper develops a system dynamics model of construction waste reduction management at the construction phase. Source reduction is an effective management measure in reducing 27.05% of total waste generation. Construction waste reduction implementation can reduce 53.77% of landfill. Illegal dumping problem is serious and it is necessary to strengthen government legislations. Abstract: A huge amount of construction waste has been generated from increasingly higher number of construction activities than in the past, which has significant negative impacts on the environment if they are not properly managed. Therefore, effective construction waste management is of primary importance for future sustainable development. Based on the theory of planned behaviors, this paper develops a system dynamic model of construction waste reduction management at the construction phase to simulate the environmental benefits of construction waste reduction management. The application of the proposed model is shown using a case study in Shenzhen, China. Vensim is applied to simulate and analyze the model. The simulation results indicate that source reduction is an effective waste reduction measure which can reduce 27.05% of the total waste generation. Sorting behaviors are a premise for improving the construction waste recycling and reuse rates which account for 15.49% of the total waste generated. The environmental benefits of source reduction outweigh those of sorting behaviors. Therefore, to achieve better environmental performance of the construction waste reduction management, attention should be paid to source reduction such as low waste technologies and on-site management performance. In the meantime, sorting behaviors encouragement such as improving stakeholders' waste awareness, refining regulations, strengthening government supervision and controlling illegal dumping should be emphasized.